School Climate and Students’ Sense of Belonging: A Literature Review, Psychosocial Mechanisms, and Practical Implications for the Indonesian Context - Winda Siregar, Tetty (Asosiasi Dosen Muda Indonesia, 2025)
This literature review synthesizes the relationship between school climate and students’ sense of belonging, encompassing definitions, dimensions, psychosocial mechanisms, mediators–moderators, and practical implications for Indonesian schools. Based on a review of English- and Indonesian-language articles from the past ±30 years, we found a consensus that school climate dimensions safety and order, the quality of teacher student and peer relationships, learning-oriented teaching practices (formative feedback, autonomy), and collaborative leadership are positively correlated with belonging. The most consistent pathways involve social support and perceived fairness/voice, which foster students’ affective attachment to school; in turn, this enhances academic engagement, achievement, and attendance while reducing risky behaviors (e.g., bullying and absenteeism). Common instruments such as the Psychological Sense of School Membership (PSSM; Goodenow) and various school climate surveys (Thapa; Wang & Degol) demonstrate strong reliability, though cross-cultural and grade-level validation in Indonesia remains limited. Practical implications recommend restorative anti-bullying programs, strengthening social-emotional learning (SEL) competencies, implementing autonomy-supportive pedagogy, and promoting student voice mechanisms aligned with the Kurikulum Merdeka and P5 initiatives. We propose a local research agenda emphasizing longitudinal or quasi-experimental studies, measurement invariance testing, and multilevel analyses.